問題文全文(内容文):
$\displaystyle \int\ 2(x-1)e^{-x}\cos\ x\ dx$
$\displaystyle \int\ e^{-x}\cos\ x\ dx=\displaystyle \frac{e^{-x}}{2}(\sin\ x-\cos\ x)+c$
$\displaystyle \int\ e^{-x}\sin\ x\ dx=-\displaystyle \frac{e^{-x}}{2}(\sin\ x+\cos\ x)+c$
$c$は積分定数
出典:広島大学
$\displaystyle \int\ 2(x-1)e^{-x}\cos\ x\ dx$
$\displaystyle \int\ e^{-x}\cos\ x\ dx=\displaystyle \frac{e^{-x}}{2}(\sin\ x-\cos\ x)+c$
$\displaystyle \int\ e^{-x}\sin\ x\ dx=-\displaystyle \frac{e^{-x}}{2}(\sin\ x+\cos\ x)+c$
$c$は積分定数
出典:広島大学
単元:
#積分とその応用#不定積分#数学(高校生)#数Ⅲ
指導講師:
ますただ
問題文全文(内容文):
$\displaystyle \int\ 2(x-1)e^{-x}\cos\ x\ dx$
$\displaystyle \int\ e^{-x}\cos\ x\ dx=\displaystyle \frac{e^{-x}}{2}(\sin\ x-\cos\ x)+c$
$\displaystyle \int\ e^{-x}\sin\ x\ dx=-\displaystyle \frac{e^{-x}}{2}(\sin\ x+\cos\ x)+c$
$c$は積分定数
出典:広島大学
$\displaystyle \int\ 2(x-1)e^{-x}\cos\ x\ dx$
$\displaystyle \int\ e^{-x}\cos\ x\ dx=\displaystyle \frac{e^{-x}}{2}(\sin\ x-\cos\ x)+c$
$\displaystyle \int\ e^{-x}\sin\ x\ dx=-\displaystyle \frac{e^{-x}}{2}(\sin\ x+\cos\ x)+c$
$c$は積分定数
出典:広島大学
投稿日:2021.08.30